2020
DOI: 10.12968/bjon.2020.29.2.s35
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the DIVA score for experienced emergency department technicians

Abstract: Background: The DIVA score is validated for predicting success of the initial attempt at peripheral intravenous insertion by nurses and physicians. A score of 4 or greater is 50% to 60% likely to have a failed first attempt. The study objective was to assess the validity of this score for emergency department technicians. Methods: This study used a prospective convenience sample of 181 children presenting to the emergency department with intravenous access attempt by one of 29 emergency department technicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Excluding so-called beginner period attempts which results in 25%-50% failure rate, PIVA attempts are almost always successful. [2][3][4][5][6] But majority of these patients require two or more attempts to establish a sound PIVA. 7 Multiple attempts to establish a successful PIVA may lead to some problems including lifelong needle fear in the child, a negative quality perception about the institution and the care delivered to patients' parents, unnecessary distress for the practicing health-care worker and increased possibility of medical complications.…”
Section: Introductionmentioning
confidence: 99%
“…Excluding so-called beginner period attempts which results in 25%-50% failure rate, PIVA attempts are almost always successful. [2][3][4][5][6] But majority of these patients require two or more attempts to establish a sound PIVA. 7 Multiple attempts to establish a successful PIVA may lead to some problems including lifelong needle fear in the child, a negative quality perception about the institution and the care delivered to patients' parents, unnecessary distress for the practicing health-care worker and increased possibility of medical complications.…”
Section: Introductionmentioning
confidence: 99%
“…The DIVA score's test characteristics in our study sample also were similar to the original study, which showed a 50% to 60% likelihood of failed first attempt when using this score, hence providing added external validation of the DIVA score 3 . Studies by Riker et al, 4 Girotto et al, 12 and Shaukat et al 13 also have externally validated the DIVA score 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…No articles classified as level I (systematic review or metaanalysis of multiple randomized controlled clinical studies) or level III (almost experimental studies -without randomization) were found. Most articles were level VI (descriptive or qualitative research) 63% [1][2]5,[16][17][18][19][20][21][22][23][24] ; followed by 21% of level IV articles (case-control and cohort studies) [25][26][27][28] , and levels II (individual studies with controlled and randomized experimental design) 4 , V (systematic reviews of descriptive (non-experimental) or qualitative studies) 29 and VII (expert opinions) 30 with 5% each 9 . Continuing the analyses of each article, Chart 1 was prepared for better visualization of participants and objectives related to the CIP.…”
Section: /18mentioning
confidence: 99%
“…In view of nursing as the main promoter of PIC, the score Difficult Intravenous Access (DIVA) was developed in English, translated to Portuguese as a Score of Difficult Intravenous Access (DIVA score) in pediatrics. This score analyzes the visibility of the vein after the tourniquet as: visible (zero points) and not visible (2 points); palpability of the vein after tourniquet as palpable (zero points) and non-palpable (2 points); age of the child: greater than or equal to 36 months of age (zero points), 12 to 35 months (1 point) and less than 12 months (3 points); prematurity: history of term birth (zero points) and premature -gestational age less than 38 weeks at birth (3 points); skin tone: light (zero points) and dark (1 point) [22][23] .…”
Section: Nursing Promoting Care In Children With Picmentioning
confidence: 99%
See 1 more Smart Citation